A study on VEGFR-2 Expression in Canine Mammary Tumors - Nistala, Raghavendra S.; Venkataswamy, Girish K.; Kumar, Kamisetty A.; Thejaswini, Gundam (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Angiogenesis is one of the hallmarks of cancer, and VEGFR-2, the receptor for VEGF is said to be more responsible for tumor angiogenesis  than the other receptors. The objective of the present study was to examine the VEGFR-2 expression in different grades of tumors with  the help of quantitative PCR. Expression profiling was studied as part of the work in VEGFR-2 with HPRT-1 gene as endogenous control  using qPCR. RNA extracted from different grades of Canine Mammary Tumors (CMTs) were used for the study. VEGFR-2 expression  was found to be overexpressed as the grade of the tumor increase, which establishes the dependency of the high grade tumors on  angiogenic factors, which in turn indicates that angiogenic factors are indispensable for angiogenesis for enhanced angiogenesis  tumor tissue proliferation.
Keywords: Angiogenesis Canine Mammary Tumors; qPCR; VEGFR-2